2021
DOI: 10.1186/s13007-021-00757-y
|View full text |Cite
|
Sign up to set email alerts
|

Methodology: non-invasive monitoring system based on standing wave ratio for detecting water content variations in plants

Abstract: Background Water content variation during plant growth is one of the most important monitoring parameters in plant studies. Conventional parameters (such as dry weight) are unreliable; thus, the development of rapid, accurate methods that will allow the monitoring of water content variation in live plants is necessary. In this study, we aimed to develop a non-invasive, radiofrequency-based monitoring system to rapidly and accurately detect water content variation in live plants. The changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Thus, there is a reasonable explanation for the results of the present study. Previous research has shown that the number of occurrence records can have a strongly negative impact on Maxent’s simulated distribution of invasive species [ 38 ]. In this paper, the occurrence records of P. pinaster reached 250,000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a reasonable explanation for the results of the present study. Previous research has shown that the number of occurrence records can have a strongly negative impact on Maxent’s simulated distribution of invasive species [ 38 ]. In this paper, the occurrence records of P. pinaster reached 250,000.…”
Section: Discussionmentioning
confidence: 99%
“…As is widely known, water changes during plant growth are among the most important monitoring parameters in plant research [ 39 ]. Open water land cover indicates that such areas provide suitable temperatures and water for organisms inhabiting the surrounding environment within a certain space and time range [ 38 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dielectric properties of plant branch tissue lie between those of polar and ionic materials, and the branch tissue is viewed as a complex porous dielectric substance consisting of a mixture of gas (g), liquid (l), and solid (s) [ 28 , 29 , 30 ], whose dielectric model can be represented by the equivalent circuit diagram, as shown in Figure 2 . The total impedance of the branch tissue is: where is the total impedance of the branch tissue; , , , , and correspond to the resistance and capacitance of gas, liquid, and solid substances, respectively; and the expression for the relative permittivity of a capacitor is: where is determined by the geometry of the measuring electrode, is the vacuum permittivity ( ), is the relative permittivity, and is the capacitance.…”
Section: Methodsmentioning
confidence: 99%
“…When 100 MHz electromagnetic wave generated by the signal source is transmitted along a coaxial transmission line, the impedance of the ring probe installed at the stem does not match the impedance of the transmission line. The electromagnetic wave will be re ected when transmitted to the probe; and then the incident and the re ected waves on the transmission line will be superimposed to form a standing wave [28,29]. The peak and trough values of the standing wave signal are measured at both ends of the transmission line and the difference between the peak and trough values is calculated (Eq.…”
Section: Stvwc Measurement Principle and Sensormentioning
confidence: 99%